Klausa Relatif dalam Bahasa Indonesia dan Padanannya dalam Bahasa Mandarin - Xu Yunyu (Diterbitkan oleh Jurusan Sastra Indonesia Fakultas Ilmu Budaya Universitas Jember bekerja sama dengan Himpunan Sarjana - Kesusastraan Indonesia (HISKI), Himpunan Pembina Bahasa Indonesia (HPBI) dan Masyarakat Linguistik Indonesia (MLI), 2013)
This paper examines the basic sentence, the relative clause (called complex attributes inMandarin), the classification of relative clauses, subordinate clauses (sequence of complexattributes in Mandarin), a sentence containing a relative clause broad, and passive sentencescontaining relative clauses in Indonesian and their counterparts in Mandarin. This study looksmany similarities between Indonesian and Mandarin. Similarities and differences in the relativeclause (complex attributes) between the two languages.